Comparison of Vietnam and China Democratization (The Effect of DOI-MOI Vietnam 1987 and The China Economic Reform OF 1978) - Dongyen Hua (GoAcademica Research & Publishing, 2020)
Vietnam and China is a reality of two authoritarian states under Communism regime. As pesimistic view, both of them judge can not consolidating democracy. But the economic growth growing fastly as the result of Doi Moi policy by Vietnam in 1987 and China’s economic reformation in 1978, are the positive signal for democracy. Communist Party (VCP and CCP) challenged to defending their legetimacy by take pragmatism way to changes their economic direction and release from the Communist orthodoxy. Economic reformation is a legetimacy transformacy nased on the performance that come from ideology. The indicator of non‐institutional democracy focus on the income distribution, and the legetimacy of Communist Party used as comparative tool of democracy in China and Vietnam.